Pengaruh Promosi, Kemudahan Berbelanja, dan Kredibilitas terhadap Intensitas Pembelian di TikTok Shop pada Konsumen di Universitas Dinamika Bangsa - Leonardo Leonardo; Grace Clarissa Angel; Jessica Bestlimvya Yap; Calvin Yang; Yossinomita Yossinomita (Prosiding Seminar Nasional Ilmu Teknik, 2025)
This study aims to analyze the influence of promotion, shopping convenience, advertising, recommendation, comment, and credibility factors on purchase intensity in the TikTok Shop platform among Indonesian households. The rapid development of social commerce services requires a deep understanding of factors driving online purchasing decisions, especially among families as primary users. A quantitative approach was employed, utilizing a Likert-scale questionnaire distributed online. The sample consisted of 150 active TikTok Shop users from various household backgrounds. Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS was used to analyze the direct effects of each factor on purchase intensity. The results indicate that promotion, shopping convenience, and credibility significantly and positively influence purchase intensity, while advertising, recommendation, and comment have relatively weaker yet still relevant effects. These findings underscore the importance of effective promotional strategies, ease-of-shopping enhancements, and building platform credibility to boost purchase intensity within the household consumer segment. The practical implications can guide e-commerce practitioners and digital marketers in formulating adaptive marketing strategies in the era of social commerce.